STUDY OF THE SORPTION PROPERTIES OF MESOPOROUS MATERIALS BASED ON ALUMINUM OXIDE AND TITANIUM DIOXIDE IN CHROMATOGRAPHIC PROCESSES - Ruziev I. Kh.; Naimbaeva F. A.; Kosimov S. E.; Oltinboyeva Z. X.; Davronova B. Sh. (American Journals Publishing, 2025)
This article presents the results of a study of the sorption properties of mesoporous materials based on aluminum oxide (Al₂O₃) and titanium dioxide (TiO₂) used in chromatographic processes. The synthesis features and structural characteristics of the obtained sorbents, including their porosity, surface area and pore size distribution, are considered. By conducting model chromatographic experiments, the influence of the oxide nature, material structure and modification conditions on the efficiency of component separation is established. The mechanisms of sorption, as well as the influence of acid-base and hydrophilic properties of the surface on the selectivity of interaction with the analyzed substances are analyzed. The results indicate high promise for the use of mesoporous oxide materials as effective stationary phases for various chromatographic methods.
Keywords: Mesoporous materials, aluminum oxide, titanium dioxide, sorption properties, chromatography, stationary phase, porosity, selectivity, surface properties, sorption, SEM, sol-gel technology.